Policing and prosecuting sexual assault: inside the criminal justice system - Spohn, Cassia (Cassia Cathleen); Tellis, Katharine, 1979- (Boulder, CO, 2014)
Study of cases reported to the Los Angeles Police Department and the Los Angeles County Sheriff's Department.
Sexual assault and the criminal justice system -- Policies and practices -- Detective and prosecutor perspectives -- Case attrition and case outcomes -- False reports -- The overuse and misuse of the exceptional clearance -- Intimate partner sexual assault -- Taking sexual assault seriously -- References.
Includes bibliographical references (pages 235-241) and index.
Keywords: Sex crimes -- United States; Law enforcement -- United States; Criminal justice, Administration of -- United States